An assessment of governmental interventions in maintaining victim empowerment centres - Mbowana, Padnah Thandekile (University of Limpopo, 2016)
This study sought to investigate governmental intervention in maintaining the victim empowerment centres of the Bohlabela Municipality in Mpumalanga. The issue is contemporary and as a social worker the author can confirm that this scourge still affects our society today and understanding government interventions is useful in terms of ensuring that they work as effectively as possible to assist citizens in the discharge of their mandate. The study uses a qualitative approach. Data collection was through interviews and a questionnaire which had open-ended questions. This research design had been chosen because it has allowed to give solid descriptions and narratives to come out from the real life experiences of social workers and victims of domestic violence as well as the challenges associated with the implementation of the victim empowerment programme. To that end, a phenomenological paradigm was adopted to achieve that ambition. The findings of the study indicate that there are acute challenges which the three centres face and these include a lack of funding, poor structure and poor marketing. The recommendations provided are intended to contribute to the centres’ viability and provide effective services in the communities in which they operate. To that end, there is a need for the government to deploy more resources such as funds, infrastructure, equipment and permanent staff as well as the establishment of permanent structures at these centres to ensure their effectiveness. Additionally, the study found that there is a need for intensive and extensive publicity and marketing of the Victim Empowerment Programmes and Victim Empowerment Centres to increase their visibility and ultimately accessibility. The study found that the centres should ideally be managed by an administrator with clinical staff, a nurse and a police officer and/or a member from the judiciary and the centres should be attached to either hospitals or police stations working at extended hours.
Thesis (MPA.) -- University of Limpopo, 2016
Keywords: Government intervention; Victim empowerment centres; 353.50968; Shelters for the homeless--South Africa-Limpopo; Shelters for the homelss -- South Africa